2021
DOI: 10.1002/anie.202107481
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing an Antiviral Drug against SARS‐CoV‐2 Main Protease

Abstract: This article highlights recent pioneering work by Günther et al. towards the discovery of potential repurposed antiviral compounds (peptidomimetic and non‐peptidic) against the SARS‐CoV‐2 main protease (Mpro). The antiviral activity of the most potent drugs is discussed along with their binding mode to Mpro as observed through X‐ray crystallographic screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Extensive research has revealed that the SARS-CoV-2 main protease (M pro , also called 3C-like protease) plays an essential role in the polyprotein maturation process, offering a relevant therapeutic target that is influenced by anti-SARS-CoV-2 prodrug treatment. 33,51,52 2.1 | PF-07304814 PF-07304814, a highly selective M pro inhibitor developed by Pfizer Inc., is a novel phosphate prodrug that is metabolized intracellularly to the active form, PF-00835231; it was initially identified during 2002-2003 for the treatment of SARS-CoV and has demonstrated broad-spectrum antiviral activity in vitro and in vivo. 53 PF-00835231 exhibits strong anti-SARS-CoV-2 activity in Vero E6 cells with a halfmaximal effective concentration (EC 50 ) value of 0.23 µM without significant cytotoxicity.…”
Section: Broad-spectrum Prodrugs Targeting the Sars-cov-main Proteasementioning
confidence: 99%
“…Extensive research has revealed that the SARS-CoV-2 main protease (M pro , also called 3C-like protease) plays an essential role in the polyprotein maturation process, offering a relevant therapeutic target that is influenced by anti-SARS-CoV-2 prodrug treatment. 33,51,52 2.1 | PF-07304814 PF-07304814, a highly selective M pro inhibitor developed by Pfizer Inc., is a novel phosphate prodrug that is metabolized intracellularly to the active form, PF-00835231; it was initially identified during 2002-2003 for the treatment of SARS-CoV and has demonstrated broad-spectrum antiviral activity in vitro and in vivo. 53 PF-00835231 exhibits strong anti-SARS-CoV-2 activity in Vero E6 cells with a halfmaximal effective concentration (EC 50 ) value of 0.23 µM without significant cytotoxicity.…”
Section: Broad-spectrum Prodrugs Targeting the Sars-cov-main Proteasementioning
confidence: 99%
“…The currently approved drugs for treating the infected patients show limited and toxic side effects. Thus, more effective antiviral drugs are still urgently desired [ 1 , 2 , 3 ]. The SARS-CoV-2 main protease (Mpro), also known as 3C-like protease (3CLpro), is involved in cleaving the viral polyprotein to produce the essential viral protein required for virus replication and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the immediate availability of the M pro crystal structure, structure-based drug discovery (SBDD) techniques were promptly used to expedite the rational identification of potential M pro inhibitors [ 5 , 6 , 7 ] or to drive the repurposing of known molecules [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Many protease inhibitors of the human immunodeficiency virus (HIV) were identified as possible anti-COVID candidates [ 15 ].…”
Section: Introductionmentioning
confidence: 99%